Topological modular forms and the absence of a heterotic global anomaly - Tachikawa, Yuji (Progress of theoretical and experimental physics, 2022)
Abstract Spacetime theories obtained from perturbative string theory constructions are automatically free of perturbative anomalies, but it is not settled whether they are always free of global anomalies. Here we discuss a possible $\mathbb{Z}_{24}$-valued pure gravitational anomaly of heterotic compactifications down to two spacetime dimensions, and point out that it can be shown to vanish using the theory of topological modular forms, assuming the validity of the Stolz–Teichner conjecture.